(untitled) (Movimenta (ISSN 1984-4298), 2021)
The objective was to demonstrate the correlation of kinematics of range of motion (ROM) of ankle dorsiflexion and of hips Internal Rotation with the dynamic changes of Lower Limbs during a Step Down Test (SDT). Materials and Methods: Participated of the study 30 professional soccer male athlets of Vila Nova Esporte Clube, who were avaluated for their functional aspects and motion standard by means of the ROM test of weight-bearing ankle dorsiflexion and the SDT. After collecting data, an statistical analysis was made using the Pearson’s correlation with the level of significance (p <0,05). Result: The greater the dorsiflexion angle, greater is the Pelvic Fall during the SDT verified on the left lower limb, having a direct correlation proportion statistically sigifinificant. Probably these changes manifests consequently from a compensatory strategy of a lower extremity as the other trunk, pelvis and knee misalignments, also present in the right low limb, didn’t obtain a significant correlation, therefore the result is presented in this research in inverse proportion. Conclusion: The results obtained in this research shows that the ROM of dorsiflexion are not significantly related to the dynamic changes of lower limbs during the SDT. Only one outcome significantly correlated the pelvic fall with the increase of the ROM of dorsiflexion in the left lower limb, but due to lack of studies, this result was inconclusive. Key-words: Range of Motion, Articular. Ankle. Lower Extremity. Hip.